The Effectiveness of E-Module on Buffer Solutions to Improve Students' Higher-Order Thinking Skills and Self-Regulated Learning - Alfiyani Lestari; Sri Atun (Jurnal Tadris Kimiya, 2021)
This study aims to determine the difference between Higher Order Thinking Skills (HOTS) and Students Self Regulated Learning (SRL) before and after using e-module based on the 7E (elicit, engage, explore, explain, elaborate, evaluate, and extend) learning cycle on the buffer solution material, and to determine the percentage of its effectiveness. The research use a quasi experiment with one-group pretest-posttest design. The subjects of this research were students of natural science 11th grade in one of senior high schools in Yogyakarta. The instrument used were test in the form of HOTS pretest-posttest description question and non-test in the form of self-regulated learning questionnaire. The data analysis technique used is Hotteling's T2 test. The results showed that the significance value was 0.000 < = 0.05, then H0 was rejected. There were differences in students' HOTS and SRL before and after using e-module based on the 7E learning cycle. The effectiveness of using e-module show by HOTS and SRL simultaneously (36.8%), HOTS (25.2%), and SRL (20.5%).